A, of Analisys of Area Function Using a Geographic Information System in the Utilization of the City of Sorong, West Papua: Fungsi Kawasan Menggunakan system Informasi Geografis terhadap pemanfaatan wilayah Kota Sorong - Irnawati, Irnawati; Soekamto, Mira Herawati; Ohorella, Syarif (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to determine the physical condition of land use in fact according to the physical condition and condition of the area from the scoring of the rainfall map, slope and soil type overlaid with the 2004 land use map and regional spatial planning. This research uses descriptive qualitative data collected into the form of tables and maps in order to obtain an overview of the suitability of the function of the area with the characteristics of the area. Based on the results of the scoring analysis of the map (slope, rainfall and soil type) there are three function zoning areas namely protected area area of ​​80.36 km², forestry cultivation area area of ​​158.57 km² and non forestry cultivation area area of ​​105.56 km². While the results of the analysis of the interpretation of the iconos path/row 107-61 image map obtained 12 land use patterns in the Sorong City area in the form of primary dryland forest, secondary dryland forest, airport, primary mangrove forest, primary swamp forest, gardens, sand, settlements, dry land farming, grass/shrubs, ponds and vacant land. In accordance with the physical conditions and land use, there are three zoning functions of the area for the direction of the Sorong City spatial plan, namely a protected area of ​​165.17 km² (47.95%), a forestry cultivation area of ​​108.47 km² (31.49%) and a cultivation area non-forestry 70.84 km² (20.56%) of the total area of ​​Sorong City 344.49 km².